Agriculture at Eleven: Visual Rhetoric and News Media Portrayals of Agriculture - Annie R. Specht; Tracy Rutherford (Journal of Applied Communications, 2013)
Modern agricultural practices have become increasingly popular topics for news media outlets; thus, the growing scrutiny placed on production agriculture warrants a study of the images incorporated into television news stories of industry-related topics. Using a visual-rhetoric framework, the researchers conducted a survey of college students who were shown still images taken from a CBS Evening News broadcast about drug-resistant pathogens and their connection to antibiotic use in livestock. Participants were asked to identify the topic of the news story based on the images, to describe their affective response to that topic, and to identify the visual cues that led them to choose that topic. Content analysis revealed that no respondents correctly identified the topic of the story and that a majority aligned the images with animal mistreatment, slaughter, or welfare. Most respondents reported indifference or negative feelings about the images and topics. Based on the study, the researchers recommend further analysis of media imagery related to livestock production and increased surveillance of industry-focused stories.
Keywords: Imagery; livestock; news; television; visual rhetoric